Collaborative reflection: Professional development among friends across contexts - Haniford, Laura C.; Allison, Valerie A.; Ramirez, Laurie A. (Frontiers in Education, 2023)
This inquiry presents an illustrative case of three teacher educator researchers’ collaborative reflection process using the transcript of a virtual meeting. The researchers are long-term friends and colleagues working in different university contexts in the U.S. The case is presented and analyzed to illuminate how the triad facilitates one another’s professional development and engages in sustainable collaborative self-study research. Self-study tenets of collaboration, reflection, and critical friendship are delineated and demonstrated through excerpts from the transcript. Conclusions and recommendations are offered for teacher educators who hope to establish and maintain similar partnerships focused on promoting healthy and productive professional/personal relationships while also improving teacher education.